2005
DOI: 10.1111/j.1464-0597.2005.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Academic Life: Work Characteristics as Predictors of Student Well‐being and Performance

Abstract: La relation entre les caractéristiques du travail, le bien-être des étudiants et la performance a été évaluée à partir du modèle de Karasck & Theorell Ӷ Travail, exigences, contrôle, soutien ӷ (1990). Un échantillon d'étudiants portugais ( N = 825) a répondu à un questionnaire comprenant des mesures du contrôle et des exigences du travail universitaire, du soutien des pairs, de la satisfaction relative à la vie universitaire, de l'anxiété/dépression et des résultats aux examens. Il apparut, comme dans d'aures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
1
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 40 publications
12
104
1
21
Order By: Relevance
“…At the end, stress and burnout significantly influence of subjective well-being (Chambel & Curral, 2005). In our research we focused mainly on detection of experiencing of positive and negative emotions (as emotional part of subjective well-being).…”
Section: Problem Of Statementmentioning
confidence: 99%
“…At the end, stress and burnout significantly influence of subjective well-being (Chambel & Curral, 2005). In our research we focused mainly on detection of experiencing of positive and negative emotions (as emotional part of subjective well-being).…”
Section: Problem Of Statementmentioning
confidence: 99%
“…Kausar (2010) reported that higher academic workloads have a negative relationship on coping strategies in college students on managing stress. More specifically, Chambel and Curral (2005) examined the relationship between work characteristics in terms of the academic workload and student well-being and performance. They found the independent variable, academic workload, to be negatively correlated with students' academic life satisfaction and ability to manage anxiety.…”
Section: College Student Stressmentioning
confidence: 99%
“…Though the demand-control-support model (Karasek & Theorell, 1990) originally focused on workers, two recent studies have shown that the model can also be successfully used to analyse students' experiences of higher education (Cotton, Dollard & de Jonge, 2002;Chambel & Curral, 2005). The results of both studies suggest that high demands, low levels of control and low levels of support from student peers affects students' well-being negatively.…”
Section: Students Experienced Lack Of Powermentioning
confidence: 99%